Goa at work around 1850. A source-based report on labour relations in Western India under the Portuguese - Matos, P. T. de; Lucassen, Jan (2020)
This research paper is an outcome of the project Global Collaboratory on the History of Labour Relations set up by the International Institute of Social History (IISH) in Amsterdam. The project’s aim is to make a worldwide inventory of all the different types of labour relations, with all their facets and combinations, in various parts of the world during five cross-sections in time: 1500, 1650, 1800, 1900, and 1950 and 2000 for Africa.